“Digital Native” Critical Editions and Homemade School Text Analysis: The Hyper Project - Muggittu, Proff. Vincenzo; Cufalo, Domenico (Literatūra, 2017)
Nowadays, although we are living in the “Digital Era”, there still do exist many serious issues which prevent scholars, teachers and students from enjoying an actual “Digital Critical Hypertext” – fully equipped with variants, paratexts, multiple translations, linguistic analysis, notes and links, but easy to develop and/or read and which is able to overcome the issues of traditional critical editing methodologies (e.g., Lachmann’s and Bédier’s methods). This paper deals with these issues and presents HYPER, an innovative application meant for both universities and schools, designed to set up and/or read a Digital Critical Hypertext in a fully interactive, customizable and user-friendly way.
Keywords: textual scholarship; philology; textual criticism; critical edition; hypertext; TEI; JSON; TEJSON; digital humanities; educational